Partial Molar Volumes and Viscosities of Monochloroaceticacid in Acetone-Water Mixtures - NIkam, P.S.; Hasan, Mehde; Nikam, Neena; Ahire, R.R. (Asian Journal of Chemistry, 2010)
Viscosity data of monochloroacetic acid solutions in aqueous acetone at 25, 30 and 35ºC are analysed with the help of modified Jones-Dole and Vand's equations, and the density data are analysed with the help of Masson's equation. The activation parameters of viscous flow are obtained by the application of transition state theory. Results show that monochloroacetic acid acts as structure promoter in water-acetone mixtures.